English Teachers' Problem in Teaching Online Class - Mukmin Mukmin; Rizqa Dwisavira (English Education Study Program, 2022)
Abstract This study aims to determine the problems experienced by English teachers at SMA Negeri 1 Luwuk in carrying out online classes. This study uses a qualitative research method in which the researcher describes the data from the research. The data in this study were obtained by in-depth interviews on the research subject, which involved four English teachers who conducted online classes at the school. The results of this study indicate three problems, supported by previous research including the problems of Tools, Credit, and Motivation. and it can be concluded that it turns out that the Tools and Credit problems, especially in SMA Negeri 1 Luwuk only a few percent are left because almost all of the students have complete facilities or at least the students already have cellphones that support online learning. Then what is still a crucial problem during online classes is student motivation which sometimes goes up and down. Despite having complete facilities, students are sometimes too lazy to participate in online learning.